Defining employee engagement for productive research and practice - DALAL, Reeshad S. (Institutional Knowledge at Singapore Management University, 2008)
Both the applied and the academic literatures on employee engagement are unfortunately in a state of disarray. In two important areas of their otherwise admirable attempt to demarcate the construct space of employee engagement, Macey and Schneider (2008) may inadvertently have contributed to the muddle. The first is the manner in which Macey and Schneider conceptualize the psychological state of engagement, and the second is their use of term engagement as a rubric that encapsulates not only cognitive-affective but also dispositional and behavioral constructs. Clarifying these points will allow for a better definition of employee engagement. This in turn will provide a firmer basis for future research and practice in the area.